ANALISIS BIBLIOMETRIK ARTIKEL ILMIAH TENTANG PELATIHAN MELALUI PROJECT BASED LEARNING - Solihin, Solihin; Dermawati, Dermawati (Balai Diklat Keagamaan Jakarta, 2025)
This study aims to analyze the implementation of Project-Based Learning (PjBL) in training by conducting a bibliometric analysis of scientific article publications from 2021 to 2025. The study uses a mixed-methods approach, combining quantitative analysis via bibliometric mapping with VOSviewer and qualitative analysis through a systematic review of relevant literature. A total of 987 articles were analyzed to identify research trends, dominant themes, and factors influencing the successful implementation of PjBL in training contexts. The results showed a significant increase in publications on PjBL, with a focus on teacher training, vocational education, technology-based learning, and professional skills development. The bibliometric analysis produced five main clusters that indicate strong interrelations among the concepts of “model”, “PjBL”, “training program”, “AI integration”, and “competence”. Implementation barriers include institutional limitations, lack of evaluation standards, and challenges in participant motivation, while success factors include institutional support, facilitator competence, participant engagement, and a conducive learning environment. Practical implications emphasize the importance of strengthening digital infrastructure, developing data-driven curricula, and strategic partnerships to optimize future training implementation. Abstrak Penelitian ini bertujuan untuk menganalisis penerapan Project-Based Learning (PjBL) dalam pelatihan dengan melakukan analisis bibliometrik terhadap publikasi artikel ilmiah tahun 2021–2025. Penelitian menggunakan pendekatan mixed methods yang menggabungkan analisis kuantitatif berupa pemetaan bibliometrik melalui VOSviewer dan analisis kualitatif melalui kajian sistematis terhadap literatur relevan. Sebanyak 987 artikel dianalisis untuk mengidentifikasi tren penelitian, tema dominan, serta faktor-faktor yang memengaruhi keberhasilan penerapan PjBL dalam konteks pelatihan. Hasil penelitian menunjukkan peningkatan signifikan dalam jumlah publikasi terkait PjBL dengan fokus pada pelatihan guru, pendidikan vokasi, pembelajaran berbasis teknologi, dan pengembangan keterampilan profesional. Analisis bibliometrik menghasilkan lima klaster utama yang menunjukkan saling terkait erat antara konsep “model”, “PjBL”, “training program”, “AI integration”, dan “competence”. Hambatan implementasi mencakup keterbatasan kelembagaan, kurangnya standar evaluasi, dan tantangan motivasi peserta, sedangkan faktor keberhasilan meliputi dukungan institusional, kompetensi fasilitator, keterlibatan peserta, serta lingkungan belajar yang kondusif. Implikasi praktisnya menekankan pentingnya penguatan infrastruktur digital, pengembangan kurikulum berbasis data, dan kemitraan strategis untuk mengoptimalkan pelaksanaan pelatihan di masa depan.